2017
DOI: 10.1177/0194599817737966
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Drug‐Induced Sleep Endoscopy Scoring Systems

Abstract: Objective To systematically review the scoring systems used to report findings during drug-induced sleep endoscopy (DISE) for adults and children with obstructive sleep apnea. Data Sources PubMed, CINAHL, EBM Reviews, Embase, and Scopus databases. Review Methods This is a systematic review of all indexed years of publications referring to scoring of DISE for children and adults with obstructive sleep apnea. The type of DISE scoring system utilized was the primary outcome. PRISMA guidelines were followed to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 43 publications
1
50
0
2
Order By: Relevance
“…A presurgical DISE could help to identify children at risk for residual OSA, and a scoring system that can aid in identifying these children would vastly improve the management of children with OSA. A systematic review of DISE scoring systems used in adults and children with OSA revealed no consensus regarding which scoring system should be utilized to report findings during DISE for adult and children with OSA . Standardization of DISE findings would be useful to improve comparability among studies and improve the quality of outcomes research for sleep surgery .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A presurgical DISE could help to identify children at risk for residual OSA, and a scoring system that can aid in identifying these children would vastly improve the management of children with OSA. A systematic review of DISE scoring systems used in adults and children with OSA revealed no consensus regarding which scoring system should be utilized to report findings during DISE for adult and children with OSA . Standardization of DISE findings would be useful to improve comparability among studies and improve the quality of outcomes research for sleep surgery .…”
Section: Discussionmentioning
confidence: 99%
“…8 Standardization of DISE findings would be useful to improve comparability among studies and improve the quality of outcomes research for sleep surgery. 8 We evaluated the utility of DISE scoring systems in the assessment of OSA using a single cohort of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations